The role of polyphenols in causing cardiovascular disease - Yenny, Yenny; Herwana, Elly (Faculty of Medicine, Trisakti University, 2008)
Research on flavonoids has increased since the discovery of the French Paradox, the low cardiovascular mortality rate observed in Mediterranean population in association with red wine consumption and a high saturated fat intake. Plant polyphenol (flavonoid) occurs naturally in fruits, vegetables, and beverages such as tea and wine. Epidemiologic studies suggest that higher polyphenol intake from fruits and vegetables is associated with decreased risk for cardiovascular disease. The mechanisms explaining this observation remain unclear. The vascular endothelium is a critical regulator of vascular homeostasis, and endothelial dysfunction contributes to the pathogenesis and clinical expression of coronary artery disease. Platelet aggregation is a central mechanism in the pathogenesis of acute coronary syndromes, including myocardial infarction and unstable angina. There are numerous reports suggesting that plant polyphenols improve endothelial function and inhibit platelet aggregation in humans.